Mental Health and Its Relationship with Academic Achievement in Students of Tabriz Nursing-Midwifery Faculty - Hossein Namdar areshtanab; Hossein ebrahimi; Mohammadhassan sahebihagh; Mohammad arshadi bostanabad (مجله ایرانی آموزش در علوم پزشکی, 2013)
Introduction: Nursing and midwifery students are exposed to high stress as they face multiple stressors in their educational and clinical experiences. This can threaten their mental health, which in turn, can affect their function. Considering the impact of mental health on individual performance, this study examined mental health and its relationship with academic achievement in students of Tabriz nursing-midwifery faculty. Methods: In one descriptive-analytical study, a sample of 251 Nursing and Midwifery students of Tabriz University of Medical Sciences was selected. Data were gathered by mental health questionnaire (GHQ-28). The mean scores of final term were regarded as academic achievement of students. The data were analyzed by SPSS- 11.5 using descriptive statistics (frequency, mean, and standard deviation) and inferential statistics (T-test, ANOVA and Pearson Correlation Coefficient). Results: Results showed that mean mental health scores of students participating in the study was 25.7 ±11.02. Findings showed that the highest mean was related to social function (11.84±2.9) and lowest to depression (3.5±3.83). Also a significantly negative correlation between scores of mental health and academic achievement was observed (P≤0/00, r=-0/229). Conclusion: According to the results, there was a significant relationship between mental health and academic achievement in students. It is necessary to conduct further studies about mental problems of students and activation of consultation centers.